NuRadioMC: simulating the radio emission of neutrinos from interaction to detector - Glaser, C.; García-Fernández, D.; Nelles, Anna; Alvarez-Muñiz, J.; Barwick, S. W.; Besson, D. Z.; Clark, B. A.; Connolly, A.; Deaconu, C.; de Vries, K. D.; Hanson, J. C.; Hokanson-Fasig, B.; et al. (European Physical Journal C: Particles and Fields, 2020)
NuRadioMC is a Monte Carlo framework designed to simulate ultra-high energy neutrino detectors that rely on the radio detection method. This method exploits the radio emission generated in the electromagnetic component of a particle shower following a neutrino interaction. NuRadioMC simulates everything from the neutrino interaction in a medium, the subsequent Askaryan radio emission, the propagation of the radio signal to the detector and finally the detector response. NuRadioMC is designed as a modern, modular Python-based framework, combining flexibility in detector design with user-friendliness. It includes a state-of-the-art event generator, an improved modelling of the radio emission, a revisited approach to signal propagation and increased flexibility and precision in the detector simulation. This paper focuses on the implemented physics processes and their implications for detector design. A variety of models and parameterizations for the radio emission of neutrino-induced showers are compared and reviewed. Comprehensive examples are used to discuss the capabilities of the code and different aspects of instrumental design decisions.
CRIS-Team Scopus Importer:2020-02-11